Edukasi Komunikasi Visual untuk Media Digital Museum Penerangan RI - Ma'arief, Muhammad Dicka; Putra, Marcel Eka (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2025)
The digital era 'forces' all aspects of life to modernize so they don't become outdated, except for museums. Museum Penerangan RI strives to provide the best service by utilizing digital media as a means of communication with its audience. To maximize this goal, visual communication media is also used. Therefore, this PKM was carried out to provide provision and education regarding visual communication to PKM partners, Museum Penerangan RI. Courses regarding the conceptualization of visual communication, audience segmentation, and characteristics of digital media is delivered to provide in-depth understanding to PKM partners. All courses is delivered in two stages, specifically presentation and QnA. Results of this PKM: Museum Penerangan RI staff as PKM participants were able to understand the concept of visual communication; Museum Penerangan RI staff can understand the characteristics of their audience; Museum Penerangan RI can utilize all available digital media, understand the characteristics of each digital media, create content according to the type of digital media, and maximize the function of each digital media.